Preparation method of small-size high-density microchannel
By coating photosensitive etching ink on the surface of the metal substrate and engraving the microchannel mask pattern with an ultraviolet laser printer, combined with the treatment of environmentally friendly etching liquid and defiling liquid, a small-size high-density microchannel structure was successfully prepared, solving the problem that the existing technology is difficult to achieve high-density microchannel preparation, significantly improving the boiling heat transfer performance and being suitable for industrial applications.
Patent Information
- Application Number
- CN202510193126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The prior art is difficult to achieve the simplicity, low cost, high efficiency, high precision and high scalability of small-sized high-density microchannels, which limits the further improvement of the boiling heat transfer performance of microchannels and the engineering application of high-performance microchannels.
The photosensitive etching ink is applied to the surface of the target metal substrate by spin coating, screen printing or spraying, and the microchannel mask pattern is engraved with an ultraviolet laser printer, and then etched in an environmentally friendly etching liquid. Finally, the protective coating is peeled off in the defiling liquid to form a small size and high density semi-elliptical microchannel structure.
It realizes high efficiency, low cost and simple preparation of small-size high-density microchannels. It has the advantages of precise size control, good heat transfer performance, high efficiency, strong scalability, and suitable for large-scale preparation and industrial applications, and significantly improves boiling heat transfer performance.
Smart Images

Figure HDA0005280636910000011 
Figure HDA0005280636910000012 
Figure HDA0005280636910000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microchannel enhanced phase change heat transfer, and in particular to a method for preparing a small-size high-density microchannel for enhancing boiling heat transfer. Background Art
[0002] Microchannel is a typical and high-performance microscale heat and mass transfer enhancement structure, which can effectively enhance liquid transport and phase change heat transfer process. Therefore, it is widely used in microfluidics, high heat flux cooling and electronic device thermal management. In particular, with the development trend of high power, high integration and small size of advanced devices, the heat dissipation problem has become increasingly severe. Microchannel enhanced boiling heat transfer technology is one of the best solutions and has received great attention in recent years. Because the preparation of microchannel structure on the heat transfer surface can not only increase the heat transfer area, but also promote bubble nucleation, growth and detachment, and can use the capillary wicking effect to improve the surface refilling capacity, inhibit the surface drying phenomenon under high heat flux density, thereby greatly improving the boiling heat transfer coefficient (HTC) and critical heat flux density (CHF). The structural size, cross-sectional shape and channel density of the microchannel have an important influence on the boiling heat transfer performance, and the above structural characteristics and parameters are directly subject to the preparation method of the microchannel. Therefore, optimizing the preparation method of the microchannel is of great significance for the development of high-performance microchannels and the promotion of their industrial application.
[0003] At present, in the application of enhanced boiling heat transfer, the main microchannel preparation methods include mechanical processing, ultrafast laser ablation and 3D printing. Mechanical processing is the most traditional and common preparation method, and its engineering application is relatively mature, but methods such as milling and wire cutting can only process microchannels with larger sizes. Usually, the minimum processing width of the channel and the channel wall (i.e., rib) is 0.3mm, which limits the increase of microchannel capillary pressure and channel density. Channel density refers to the number of channel roots per unit length in the direction perpendicular to the heat transfer surface. The density of mechanically processed microchannels is usually less than 17cm -1, making it difficult to further improve the boiling heat transfer performance of microchannels. In addition, when microchannels are used in phase change heat dissipation devices such as ultra-thin heat pipes and temperature equalizers, it is difficult to machine microchannels on their surfaces by mechanical processing because the thickness of the metal substrate is only 0.05-0.5mm. Ultrafast laser ablation refers to the use of femtosecond or picosecond laser systems to directly ablate microchannels on the heat transfer substrate. It has high processing accuracy and is conducive to the preparation of small-sized and high-density microchannels, but the main problem is that it relies on expensive large equipment and can only process one microchannel heat sink at a time. It also requires long-term scanning ablation to form high-performance microchannels with a large aspect ratio. Therefore, the processing efficiency is low and the cost is high. It is usually only suitable for laboratory research and some high-precision industries, and it is difficult to industrialize and mass-produce; if a relatively low-cost nanosecond laser system is used to directly ablate the microchannel, due to the easy generation of a more obvious thermal effect, the etching effect of the metal microchannel will be poor, and the substrate will be prone to thermal deformation and other problems. The 3D printing method also has high requirements for equipment and operating skills, and there are problems such as step effect, insufficient processing accuracy, difficulty in preparing metal microchannels, and insufficient structural strength. It can be seen that the existing technology is difficult to achieve the simple, low-cost, high-efficiency, high-precision and high-scalability preparation of small-sized and high-density microchannels, which is not conducive to further improving the boiling heat transfer performance of microchannels and the engineering application of high-performance microchannel enhanced heat transfer structures. Summary of the invention
[0004] The purpose of the present invention is to propose a method for preparing a small-size and high-density microchannel. The method proposed in the present invention does not require expensive large-scale professional equipment and a harsh experimental environment, and can achieve simple, convenient, low-cost and rapid preparation of small-width, high-density microchannels. It has the advantages of precise size control, good heat transfer performance, high efficiency, strong scalability, large-scale preparation and industrial application, and is particularly suitable for heat dissipation application fields such as enhanced boiling heat transfer.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a small-size high-density microchannel comprises the following steps:
[0007] Step A: ultrasonically cleaning the target metal substrate using a cleaning agent;
[0008] Step B: coating the target metal substrate with a photosensitive anti-etching ink by spin coating, screen printing or spray coating, and curing the ink to form a uniform and continuous photosensitive anti-etching protective coating on the target metal substrate, wherein the thickness of the photosensitive anti-etching protective coating is 0.2-10 μm;
[0009] Step C: using an ultraviolet laser printer to carve a microchannel mask pattern on the above-mentioned photosensitive anti-etching protective coating, the minimum line width corresponding to the ultraviolet laser printer is 1-30 μm, the area of the exposed metal surface in the microchannel mask pattern corresponds to the microchannel area formed subsequently, and the area covered by the photosensitive anti-etching protective coating stripes corresponds to the microchannel wall formed subsequently; wherein, the width of the exposed metal surface corresponding to a single microchannel in the microchannel mask pattern is 5-100 μm, and the width of the photosensitive anti-etching protective coating stripes is 40-500 μm;
[0010] Step D: Immerse the target metal substrate with the microchannel mask pattern in an environmentally friendly etching solution for etching. The environmentally friendly etching solution undergoes an oxidation-reduction reaction with the exposed metal to oxidize the metal into metal cations that fall off the substrate surface, thereby achieving an etching effect and obtaining a semi-elliptical microchannel structure with a cross section of a certain depth. For etching small-sized and high-density microchannels on a copper substrate, preferably, the environmentally friendly etching solution is an aqueous sodium chloride solution containing ammonium persulfate, wherein the concentration of ammonium persulfate is 20-140 mg / mL, and the mass ratio of sodium chloride to ammonium persulfate is 16:1-1.5:1. During the immersion etching process, the environmentally friendly etching solution is regularly subjected to ultrasonic oscillation or magnetic stirring, and the ultrasonic oscillation or magnetic stirring is performed for 2-60 seconds for every 1-5 minutes of etching.
[0011] Step E: Immerse the above-mentioned etched target metal substrate in a stripping solution that can react with the photosensitive anti-etching protective coating, so that the photosensitive anti-etching protective coating stripes are peeled off from the surface of the target metal substrate, exposing the microchannel wall, and obtaining a target metal substrate with a small-sized high-density microchannel structure. The depth of the obtained semi-elliptical microchannel is 10-140μm, the opening width is 25-300μm, and the channel density is 18-200cm -1 .
[0012] In step B of the above preparation method, the curing temperature of the photosensitive anti-etching protective coating is 60-100° C., and the curing time is 1-5 min.
[0013] In step C of the above preparation method, when the ultraviolet laser marking machine is used to engrave the microchannel mask pattern, the scanning speed of the laser is 200-1000 mm / s, and the number of scanning times is 1-10 times.
[0014] In step D of the above preparation method, the immersion etching process mainly controls the etching depth of the microchannel by etching time; in addition, the etching rate can be further regulated by rocking, bubble impact, increasing the etching solution temperature, etc., and the etching solution temperature is 20-60°C.
[0015] The beneficial effects of the present invention are as follows:
[0016] 1. The method for preparing a small-size high-density microchannel structure proposed by the present invention does not require expensive professional large-scale equipment and a harsh experimental environment. First, the photosensitive blue ink often used in the proofing of printed circuit boards (PCB boards) is selected as a protective coating in the process of etching microchannels. It has excellent corrosion resistance and its cost is much lower than the photoresist used in the standard photolithography process; at the same time, a method suitable for preparing ultra-thin coatings such as spin coating, screen printing or spraying is used to form a uniform anti-etching coating on the surface of the target metal substrate. The thickness can be controlled to be 0.2-10 μm, which can significantly reduce the time required for subsequent thermal curing, greatly improve production efficiency, and is conducive to the preparation of high-precision microchannel mask patterns. The prior art mostly uses brushing, rolling or scraping methods to prepare blue oil coatings, with a minimum thickness of about several hundred microns and poor uniformity, which is only suitable for preparing microstructures with larger size and lower density.
[0017] 2. The present invention is based on the preparation of ultra-thin blue oil protective coating, directly using common industrial ultraviolet laser marking machine to carve microchannel pattern on its surface, it utilizes the advantage that laser can quickly remove organic materials and thus mark the pattern, can complete the drawing of microchannel pattern on the blue oil coating of target metal substrate in a few seconds, so that part of the metal surface is exposed, so that it can be further etched, forming microchannels of different structural sizes, the minimum line width of the preferred industrial ultraviolet laser marking machine is generally 5-20 μm, and the line spacing is accurately adjustable, the mask pattern can be flexibly designed, and the high-precision preparation demand of multiple small-size high-density microchannel patterns can be realized. It just utilizes the characteristic that laser can quickly remove ultra-thin blue oil resin, so it avoids the problems such as low efficiency, high cost, and large thermal effect of laser direct ablation microchannel method. At the same time, there are also methods in the prior art that use patterned film to expose and develop the blue oil coating, which involves a variety of chemicals and has relatively complicated steps. It is also affected by exposure accuracy, blue oil coating adhesion strength, film and blue oil coating fit, and development process. It is usually only suitable for processing microstructures with larger size and lower density. When preparing small-size, high-density, high-precision microchannel structures, problems such as large-area development residues or mask pattern damage are prone to occur.
[0018] 3. For the processing of copper-based microchannels, the present invention preferably proposes a formula of an environmentally friendly etching solution, that is, a sodium chloride aqueous solution containing ammonium persulfate. By optimizing the ratio and concentration, it has the advantages of high etching rate and low corrosiveness to other objects. At the same time, a method of regularly ultrasonically oscillating or magnetically stirring the etching solution during the etching process is also proposed, which can effectively remove objects that hinder etching, such as reaction products and air films attached to the metal surface, and can further significantly improve the etching rate and etching uniformity. Compared with commercial etching solutions, the etching rate at room temperature can be increased from 2μm / min to 10μm / min, which is helpful to achieve high uniformity, high efficiency, high scalability, and large-scale preparation of small-size, high-density, and high-precision microchannels, and is suitable for engineering applications.
[0019] 4. The copper etching solution proposed in the invention can spontaneously form a semi-elliptical microchannel structure with a rough channel surface due to anisotropic etching and specific chemical reaction characteristics. Compared with the rectangular and inverted triangle channels often formed by mechanical processing and laser direct ablation, it has better performance in terms of pressure drop, heat transfer efficiency and stability; at the same time, the numerous micro-nano structures generated on the channel surface will further increase the heat transfer area and strengthen the bubble dynamics behavior, which is conducive to further improving the boiling heat transfer performance. Experimental tests show that the channel density prepared by the present invention is 61cm -1 The surface of the semi-elliptical microchannel structure with a depth of 30 μm has a CHF and a maximum HTC of 206 W cm -2 and 11.3W cm -2 K -1 , which are increased by 142% and 250% respectively compared with the copper plane, showing a significant boiling heat transfer enhancement effect.
[0020] In summary, the method for preparing small-size and high-density microchannels proposed in the present invention has the advantages of high dimensional accuracy, fast etching rate, simplicity, high efficiency, low cost, strong scalability, large-scale preparation and engineering application, and has broad prospects in the fields of microfluidics, high heat flow cooling and thermal management of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0022] Figure 1 This is an optical photograph of the microchannel structure sample prepared in Example 2 of the present invention, and its channel density is 19 cm -1 , the channel depth is 90±2μm, the channel opening width is 280±4μm, and the top width of the channel wall is 220±4μm.
[0023] Figure 2This is a comparison chart of the saturated pool boiling heat transfer performance of two different boiling surfaces, the microchannel surface 1 and the smooth copper plane in Example 2 of the present invention, under normal pressure with deionized water as the working fluid, (a) is the boiling curve, and (b) is the heat transfer coefficient curve.
[0024] Figure 3 This is an optical photograph of the microchannel structure sample prepared in Example 3 of the present invention, and its channel density is 61cm -1 , the channel depth is 30±2μm, the channel opening width is 90±4μm, and the top width of the channel wall is 60±4μm.
[0025] Figure 4 This is a comparison diagram of the saturated pool boiling heat transfer performance under normal pressure using deionized water as the working fluid for three different boiling surfaces, namely, the microchannel surface 2 in Example 3 of the present invention, the microchannel surface 1 in Example 1, and the smooth copper plane. (a) is the boiling curve and (b) is the heat transfer coefficient curve. DETAILED DESCRIPTION
[0026] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0027] Example 1
[0028] The channel density is 25 cm on the copper substrate. -1 The semi-elliptical microchannel structure comprises the following steps:
[0029] Step A: ultrasonically clean a round copper sheet with a diameter of 10 mm and a thickness of 1 mm using a cleaning agent;
[0030] Step B: coating the surface of the target metal substrate with photosensitive anti-etching blue oil by spraying, the blue oil thickness is 800nm, and thermally curing at 90°C for 1min to form a uniform blue oil protective coating on the surface of the target metal substrate;
[0031] Step C: Use an ultraviolet laser marking machine to design a microchannel pattern, which consists of 25 parallel lines with a line spacing of 380μm. Perform laser rapid scanning on the blue oil coating of the target metal substrate to engrave the microchannel pattern. The scanning speed is 1000mm / s and the number of scans is 1. In the formed microchannel mask pattern, the width of the area exposed on the metal surface is 30μm. In the subsequent wet etching process, the microchannel is formed. The width of the area covered by the blue oil coating stripes is 350μm, corresponding to the microchannel wall formed subsequently;
[0032] Step D: A total of three target metal substrate samples with microchannel patterns were prepared. Sample 1 was immersed in a commercial copper-friendly etching solution and was slightly shaken periodically during the etching process as a comparison with a conventional etching scheme; Sample 2 was immersed in a sodium chloride aqueous solution containing ammonium persulfate, the ammonium persulfate concentration was 100 mg / mL, and the mass ratio of sodium chloride to ammonium persulfate was 7:3. During the etching process, it was slightly shaken periodically; Sample 3 was immersed in a sodium chloride aqueous solution containing ammonium persulfate, the ammonium persulfate concentration was 100 mg / mL, and the mass ratio of sodium chloride to ammonium persulfate was 7:3. During the etching process, the etching solution was ultrasonically oscillated for 10 seconds every 2 minutes; all three samples were etched at room temperature, and the etching time was 5 minutes.
[0033] Step E: Immerse the target metal substrate after the above etching in a stripping solution that can react with the photosensitive anti-etching protective coating, so that the blue oil coating stripes are peeled off from the surface of the target metal substrate, exposing the microchannel wall, and 25 semi-elliptical microchannels are prepared on the target metal substrate with a diameter of 10 mm. The channel depths of the three samples are 10μm, 25μm and 50μm, respectively. The etching rates corresponding to the three technical schemes are 2μm / min, 5μm / min and 10μm / min, respectively.
[0034] Example 2
[0035] The channel density on the target metal substrate is 19 cm -1 , a semi-elliptical microchannel structure with a depth of 90 μm, comprising the following steps:
[0036] Step A: ultrasonically clean a round copper sheet with a diameter of 10 mm and a thickness of 1 mm using a cleaning agent;
[0037] Step B: coating the surface of the target metal substrate with photosensitive anti-etching blue oil by screen printing, with a thickness of 10 μm, and thermally curing at 60° C. for 5 min to form a uniform blue oil protective coating on the surface of the target metal substrate;
[0038] Step C: Use an ultraviolet laser marking machine to design a microchannel pattern, which consists of 19 parallel rectangles, with a rectangular pattern width of 100 μm and a center spacing of 500 μm. Perform laser rapid scanning on the blue oil coating of the target metal substrate to engrave the microchannel pattern, with a scanning speed of 600 mm / s and a scanning number of 1. In the formed microchannel mask pattern, the width of the area where the metal surface is exposed is 100 μm. In the subsequent wet etching process, a microchannel is formed, and the width of the area covered by the blue oil coating stripes is 400 μm, corresponding to the microchannel wall formed subsequently;
[0039] Step D: Immerse the target metal substrate with the microchannel pattern in a sodium chloride solution containing ammonium persulfate, wherein the concentration of ammonium persulfate is 100 mg / mL and the mass ratio of sodium chloride to ammonium persulfate is 7:3. Wet etching is performed at room temperature for 18 minutes. Periodic shaking is performed during the etching process to accelerate the contact between the reactants and the metal, and also to promote the reaction products to be separated from the metal surface in time, thereby improving the etching uniformity and rate. Due to the isotropic etching characteristics, a semi-elliptical microchannel structure will eventually be etched.
[0040] Step E: Immerse the target metal substrate that has been etched as above in a stripping solution that can react with the photosensitive anti-etching protective coating, so that the blue oil coating stripes are peeled off from the surface of the target metal substrate, exposing the microchannel wall, and preparing 19 semi-elliptical microchannels on the target metal substrate with a diameter of 10 mm. The channel depth is 90±2μm, the channel opening width is 280±4μm, and the top width of the channel wall is 220±4μm.
[0041] The saturated pool boiling heat transfer test was carried out on the microchannel surface. The liquid working medium was deionized water, the test pressure was normal pressure, and the smooth copper plane was used as the reference sample. Figure 2 This is a comparison chart of saturated pool boiling performance. Figure 2 (a) is the boiling curve. Figure 2 (b) is the heat transfer coefficient curve, Figure 2 It can be seen that the boiling performance of the microchannel surface is significantly better than that of the ordinary copper plane, and the CHF and maximum HTC are increased by 125% and 197% respectively compared with the copper plane, which confirms its beneficial effects and shows important application prospects in the fields of thermal energy conversion, utilization and management.
[0042] Example 3
[0043] The channel density on the target metal substrate is 61cm -1 , a semi-elliptical microchannel structure with a depth of 30 μm, comprising the following steps:
[0044] Step A: ultrasonically clean a round copper sheet with a diameter of 10 mm and a thickness of 1 mm using a cleaning agent;
[0045] Step B: Spin coating the target metal substrate with photosensitive anti-etching blue oil, the blue oil thickness is 5 μm, and heat curing is performed for 3 minutes at a curing temperature of 80° C., so that a uniform blue oil protective coating is formed on the target metal substrate surface;
[0046] Step C: Design the microchannel pattern using an ultraviolet laser marker, and perform laser rapid scanning on the blue oil coating of the target metal substrate to engrave the microchannel pattern, with a scanning speed of 800 mm / s and a scanning number of 1. In the formed microchannel pattern, the width of the area exposed on the metal surface is 30 μm, and the microchannel is formed in the subsequent wet etching process. The width of the area covered by the anti-etching coating stripes is 120 μm, corresponding to the microchannel wall formed subsequently;
[0047] Step D: Immerse the target metal substrate with the microchannel pattern in a sodium chloride solution containing ammonium persulfate, wherein the concentration of ammonium persulfate is 100 mg / mL and the mass ratio of sodium chloride to ammonium persulfate is 7:3. Wet etching is performed at room temperature for 3 minutes. During every 1 minute of etching, the etching solution is magnetically stirred for 20 seconds at a rotation speed of 500 rpm, which can effectively remove objects that hinder etching, such as reaction products and air films attached to the metal surface, and can further significantly improve the etching rate and etching uniformity.
[0048] Step E: Immerse the target metal substrate after the etching in a stripping solution that can react with the photosensitive anti-etching protective coating, so that the blue oil coating stripes are peeled off from the surface of the target metal substrate, exposing the microchannel wall, and preparing 61 semi-elliptical microchannels on the target metal substrate with a diameter of 10 mm. The channel depth is 30±2μm, the channel opening width is 90±4μm, and the rib top width is 60±4μm.
[0049] The saturated pool boiling heat transfer test was performed on the microchannel surface. The liquid working medium was deionized water. The test pressure was normal pressure. The smooth copper plane and the microchannel surface prepared in Example 1 were used as reference samples. Figure 4 This is a comparison chart of saturated pool boiling performance. Figure 4 (a) is the boiling curve. Figure 4 (b) is the heat transfer coefficient curve, Figure 4 It can be seen that the boiling performance of the microchannel surface is significantly better than that of the ordinary copper plane, and its CHF and maximum HTC are 206 W cm -2 and 11.3W cm -2 K -1 , compared to 85W cm for copper plane -2 and 3.2W cm -2 K -1 , respectively increased by 142% and 250%; in addition, it can be seen that when the channel density is greatly increased, even if the channel depth is only one-third of the microchannel in Example 1, its boiling heat transfer performance can be further enhanced, confirming the beneficial effect of small-sized and high-density microchannels. Using the method proposed in the present invention, a small-sized and high-density microchannel structure can be easily prepared on the metal substrate of an ultra-thin heat transfer device, which has excellent boiling heat transfer performance.
[0050] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a small-size high-density microchannel, characterized in that: The following steps are involved: Step A: ultrasonically cleaning the target metal substrate using a cleaning agent; Step B: coating the target metal substrate with a photosensitive anti-etching ink by spin coating, screen printing or spray coating, and curing the ink to form a uniform and continuous photosensitive anti-etching protective coating on the target metal substrate, wherein the thickness of the photosensitive anti-etching protective coating is 0.2-10 μm; Step C: using an ultraviolet laser printer to carve a microchannel mask pattern on the above-mentioned photosensitive anti-etching protective coating, the minimum line width corresponding to the ultraviolet laser printer is 1-30 μm, the area of the exposed metal surface in the microchannel mask pattern corresponds to the microchannel area formed subsequently, and the area covered by the photosensitive anti-etching protective coating stripes corresponds to the microchannel wall formed subsequently; wherein, the width of the exposed metal surface corresponding to a single microchannel in the microchannel mask pattern is 5-100 μm, and the width of the photosensitive anti-etching protective coating stripes is 40-500 μm; Step D: Immerse the target metal substrate with the microchannel mask pattern in an environmentally friendly etching solution for etching. The environmentally friendly etching solution undergoes an oxidation-reduction reaction with the exposed metal to oxidize the metal into metal cations that fall off the substrate surface, thereby achieving an etching effect and obtaining a semi-elliptical microchannel structure with a cross section of a certain depth. For etching small-sized and high-density microchannels on a copper substrate, preferably, the environmentally friendly etching solution is an aqueous sodium chloride solution containing ammonium persulfate, wherein the concentration of ammonium persulfate is 20-140 mg / mL, and the mass ratio of sodium chloride to ammonium persulfate is 16:1-1.5:
1. During the immersion etching process, the environmentally friendly etching solution is regularly subjected to ultrasonic oscillation or magnetic stirring, and the ultrasonic oscillation or magnetic stirring is performed for 2-60 seconds for every 1-5 minutes of etching. Step E: Immerse the above-mentioned etched target metal substrate in a stripping solution that can react with the photosensitive anti-etching protective coating, so that the photosensitive anti-etching protective coating stripes are peeled off from the surface of the target metal substrate, exposing the microchannel wall, and obtaining a target metal substrate with a small-sized high-density microchannel structure. The depth of the obtained semi-elliptical microchannel is 10-140μm, the opening width is 25-300μm, and the channel density is 18-200cm -1 .
2. The method according to claim 1, characterized in that In step B of the above preparation method, the curing temperature of the photosensitive anti-etching protective coating is 60-100° C., and the curing time is 1-5 min.
3. The method according to claim 1, characterized in that In step C of the above preparation method, when the ultraviolet laser printer is used to engrave the microchannel mask pattern, the scanning speed of the laser is 200-1000 mm / s, and the number of scanning times is 1-10 times.
4. The method according to claim 1, characterized in that In step D of the above preparation method, the immersion etching process mainly controls the etching depth of the microchannel by etching time.
5. The method according to claim 1, characterized in that In addition, the etching rate can be further controlled by using methods such as shaking, bubble impact, and increasing the temperature of the etching solution, and the temperature of the etching solution is 20-60°C.
6. A small-size, high-density microchannel prepared according to the method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Method for rapidly manufacturing silicon microchannel by using laser induction and wet etching
CN117285002A
Graded carbon nanomaterial thin film coating for strengthening boiling heat transfer and preparation method of graded carbon nanomaterial thin film coating
CN117757290A
Methods and apparatus for ink delivery to nanolithographic probe systems
WO2004044552A2
Structure comprising microchannel, production method for said structure, and microchannel device
WO2023068276A1